ANALYSIS OF FOOD WASTE CAMPAIGN CONTENT ON THE HASHTAG #HABISKANMAKANANMU ON INSTAGRAM - Indah Ageng Maulidini; Ujang Sumarwan (Journal of Child, Family, and Consumer Studies, 2022)
The rise of food waste issues has prompted the implementation of several social campaigns, one of which is the #HabiskanMakananmu social campaign. This study aims to identify the characteristics and analyze the effectiveness of social campaign content on #HabiskanMakananmu on Instagram. This research is an exploratory design with a content analysis method. The data collection used a purposive sampling technique of 200 social campaign content on Instagram using the content analysis method. The data was processed by cross-tabulation and descriptive interpretation using Microsoft Excel, IBM SPSS Statistics 25.0, and Voyant web as a qualitative data processing application. The results of content effectiveness show that most of the content is interesting, uses standard language in delivering messages, contains two to three pieces of information, creates a sense of awareness and sympathy for readers, and has the potential to change reader behavior. Therefore, content readers can choose and read content wisely and apply habits that reduce food waste.